Analisis Kesadaran Lingkungan, Ekuitas Merek, dan Pemasaran Digital Terhadap Keputusan Pembelian Produk Hijau: (Studi Kasus Konsumen Wilayah Grogol, Jakarta Barat) - Achmad Tarmizi; Dian Meliantari (CV. Ulil Albab Corp, 2025)
This study aims to determine the positive influence of Environmental Awareness, Brand Equity, and Digital Marketing on Purchase Decisions for Green Products: A Case Study of Consumers in the Grogol Area, West Jakarta. Data collection in this study was conducted using a survey method by distributing 100 questionnaires. The sampling technique used in this research is accidental sampling. Accidental sampling is a method of determining the sample size when the exact population size is unknown. This study employs multiple regression analysis using SPSS version 26 as the tool to process and analyze the research results. The hypothesis test results show that the Environmental Awareness variable has a significant effect on Green Product Purchase Decisions. The Brand Equity variable has a significant effect on Green Product Purchase Decisions. The Digital Marketing variable has a significant effect on Green Product Purchase Decisions. Furthermore, the Environmental Awareness, Brand Equity, and Digital Marketing variables simultaneously have a significant effect on Green Product Purchase Decisions